Penguatan Nilai-Nilai Kewarganegaraan pada Era Globalisasi Melalui Pendidikan dalam Kehidupan Bermasyarakat - sharah; sharah, sharah; Naim, Jannatun; Larasati, Dinda; Yanti, Dian AJeng Dewa (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2025)
This research aims to reposition the values of Civic Education (PKn) in the life of society, nation, and state. The research method used is literature review. The results of the study show that the noble values of Pancasila have declined due to globalization, so it is necessary to revitalize them through the replanting of Pancasila values in civic education. This study has advantages in relevant objectives and the use of qualitative methods, but also has shortcomings in limited samples and unclear data collection methods. This research is useful in improving the quality of education, shaping the nation's character, and creating a better society. the community actively in every process of implementing the preservation strategy. Although this study has some limitations, such as a limited sample and unclear data collection methods, The results of this study can provide a useful picture for the development of civic education and strategies for the preservation of national values. In addition, this research has great benefits for the world of education, society, and individuals in increasing awareness, quality, and positive contributions in community. In addition, this research has great benefits for the world of education, society, and individuals in increasing awareness, quality, and positive contributions in community life.